INSTRUCTIONS ENHANCING CLASSROOM ENGAGEMENT: THE IMPACT OF LEARNING STYLES ON FRESHMEN OF TEACHER COLLEGE - Rosma Indriana Purba; Carmel Serafim Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Understanding one’s learning style is crucial for improving students’ learning processes. However, many educators and students remain unaware of its significance. This research investigates the relationship between teaching strategies and student engagement in the 2023 cohort of the International Teachers College (ITC). Additionally, it explores the extent to which awareness of learning styles supports ITC freshmen in their learning process. The study surveyed 15 freshmen at ITC using an online questionnaire with 25 rating-scale items. The findings indicate that students are more engaged and motivated when their learning styles are considered in the classroom, with motivation scoring 3.44 out of 4. Comprehension is also affected, scoring 3.33 out of 4 when students learn in their preferred style. Students retain information better when using appropriate learning aids. Lastly, the study found that students' self-efficacy, scoring 3.15 out of 4, is often influenced by their learning styles, making them more active and productive in completing tasks